4 - Public Sphere and Epistemologies of the South - Santos, Boaventura de Sousa (Africa Development, 2021)
The ‘public sphere’ is one of the key concepts of the social theory produced in the global North. But does the global South need this concept? Its theoretical and cultural presuppositions are entirely European. They are not necessarily universally valid, even when they purport to be general theories. If the epistemological diversity of the world is to be accounted for, other theories must be developed and anchored in other epistemologies – the epistemologies of the South that adequately account for the realities of the global South. This paper is a meta-theoretical critique of the concept of the public sphere from the standpoint of the need for this epistemological diversity. It emphasises the need for intercultural translation, understood as a procedure that allows for mutual intelligibility among the diverse experiences of the world. Such a procedure does not endow any set of experiences with the statute either of exclusive totality or homogenous part. In the African context, this work of translation involves two moments. First, a deconstructive challenge which consists in identifying the Eurocentric remains inherited from colonialism. Secondly, a reconstructive challenge which consists in revitalising the historical and cultural possibilities of the African legacy, interrupted by colonialism and neocolonialism. In this twofold movement of social experiences relations of mutual intelligibility emerge which must not result in the cannibalisation of some by others.